2019
DOI: 10.3390/nu11020413
|View full text |Cite
|
Sign up to set email alerts
|

Poor Iodine Knowledge, Coastal Region, and Non-Iodized Salt Consumption Linked to Low Urinary Iodine Excretion in Zhejiang Pregnant Women

Abstract: Background: Iodine deficiency in pregnant women, defined as a median urinary iodine concentration (UIC) of less than 150 μg/L, is an important public health issue. To improve their iodine intake, it is important to understand the knowledge and practices regarding iodine. Methods: A cross-sectional investigation was conducted on 2642 pregnant women during 2016–2017 in Zhejiang province, China. A 3-point Likert scale questionnaire was used to record knowledge. The UIC and iodine content in household salt were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 24 publications
(31 reference statements)
1
28
0
Order By: Relevance
“…The geographical variations in the percentage of households using iodized salt may be related to the differences in knowledge and attitude regarding the consumption of iodized salt between coastal and inland inhabitants. Our previous study showed that inhabitants from the coastal areas had a widespread incorrect perception that iodine-rich seafood (e.g., seaweed and marine fish) was more natural and safer than iodized salt when asked why seafood was chosen as the preferred source of iodine [20]. Consequently, costal inhabitants who consume seafood are reluctant to buy iodized salt.…”
Section: Discussionmentioning
confidence: 99%
“…The geographical variations in the percentage of households using iodized salt may be related to the differences in knowledge and attitude regarding the consumption of iodized salt between coastal and inland inhabitants. Our previous study showed that inhabitants from the coastal areas had a widespread incorrect perception that iodine-rich seafood (e.g., seaweed and marine fish) was more natural and safer than iodized salt when asked why seafood was chosen as the preferred source of iodine [20]. Consequently, costal inhabitants who consume seafood are reluctant to buy iodized salt.…”
Section: Discussionmentioning
confidence: 99%
“…Since more than 90% iodine intake excrete from urine, the disparity in the median UIC between these two regions can be explained by the difference in iodine intake which may be influenced by two factors. First, the coastal population hold widespread misconception that non-iodized salt is one sort of natural salt and more healthy than iodized salt 6 . They are more likely to consume non-iodized salt than those from the inland 6 , as seen from the coverage of household iodized salt, which is usually lower in the coast (61.9–64.3%) when compared with the inland (95.1–95.3%) 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the causes of thyroid abnormalities plays a critical role on maintaining the implementation of USI for the increasing number of cases with thyroid abnormalities would lose confidence in consumption of iodized salt 6 , which may ultimately result in IDD re-emerging 7 . Previously published studies on the causes of thyroid abnormalities, however, remain inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…", were also included (Supplementary 1). These validated questions were adapted from previous studies [13,15,16]. In addition, these questions were further validated in our setting and pilot tested in order to check for validity, comprehension, and clarity.…”
Section: Assessment Of Iodine Knowledge Levelmentioning
confidence: 99%